(untitled) (Journal of Nepal Physical Society, 2024)
The perovskite compound LaMnO3 has gained interest due to its role as a fundamental building block in some heterostructures and its fascinating magnetic phase diagram. In Bulk stoichiometric form, LMO displays A-type antiferromagnetic order. However, thin films exhibit ferromagnetic properties and spontaneous magnetization reversal for zero field cooled (ZFC) magnetization cycles. Our study examined the field-dependent variation of blocking (TB ), freezing (Tf ), and compensation (Tcomp ) temperature associated with the ZFC cycle. The blocking temperature follows the relation TB (H) = TB (0)(1 − H/HK )2 , typical of magnetic nanoparticles indicating nanoclusters of spins in the thin film. The freezing and compensation temperatures exhibited exponential decay with increasing field. We examined the temperature dependence of coercivity and exchange bias. The observed trend in coercivity, combined with the absence of exchange bias, supports the presence of a mixture of weakly interacting superparamagnetic and antiferromagnetic phases. Below the blocking temperature coercivity follows the relationship HC (T ) = HC0 [1 − (T /TB )1/2 ].